“Exorcist illusion”: Twisting necks in the hollow-face and hollow-torso illusions - Papathomas, Thomas V. (Pion, 2012)
We combine a convex facial mask with a concave torso—or vice versa—thus creating a single rigid object with a transition area at the neck, where convexity changes to concavity. This combination creates stunning illusions when the rigid object is set to motion. The two simplest effects are (1) when the object is rotated about its axis, the head appears to twist with respect to the torso, as in “The Exorcist” film; (2) when it is rotated around an axis parallel to the shoulders, the head appears to hinge around the torso. More complex illusory effects result from more complex motions. The involvement of higher-level perceptual processes may account for the illusory effects.